The Happiness at Work Affecting to Loyalty to Food and Beverage Manufacturing Organization - Klinmahom, Suphadanai; Chuacharoen, Orathai (Journal for Developing the Social and Community, 2025)
Background and Aims: In the food and beverage manufacturing industry, employees’ happiness at work often stems from a safe environment, fair management, and recognition of their contributions. This sense of happiness is directly linked to positive employee attitudes, which in turn fosters organizational loyalty. This study aims to: 1) Examine the personal factors, work happiness, and organizational loyalty of employees in food and beverage manufacturing organizations; 2) Investigate the personal factors that affect organizational loyalty in food and beverage manufacturing organizations; and 3) Explore how work happiness influences organizational loyalty in food and beverage manufacturing organizations. Methodology: This study employed a quantitative research approach. The sample consisted of 400 employees working in food and beverage manufacturing organizations. The statistical methods used for data analysis included descriptive statistics such as frequency, percentage, mean, and standard deviation, as well as inferential statistics including t-test, F-test, and multiple regression analysis. Results: 1) The majority of the respondents were female, with most falling within the age range of 26–35 years. Their average monthly income ranged between 20,001 and 30,000 baht, and most had been working for a period of 1 to 4 years. 2) Personal factors such as gender, age, and length of service did not significantly affect their happiness in life. However, differences in monthly income had a statistically significant effect on organizational loyalty in food and beverage manufacturing organizations at the 0.05 level. 3) Work happiness, particularly in five out of eight aspects, significantly influenced employee loyalty. The aspect of “Inner Peace” had the greatest overall impact on loyalty to food and beverage manufacturing organizations, while the aspect of “social well-being” had the least impact, with statistical significance at the 0.05 level. Conclusion: Most employees in the food and beverage manufacturing organization report a high level of job satisfaction, particularly in terms of inner peace, which greatly influences their loyalty to the organization. Meanwhile, variations in monthly income have a noticeable effect on the degree of loyalty. Therefore, the organization should promote both mental well-being and a positive work environment to cultivate sustainable commitment to cultivate sustainable commitment, thereby reducing employee turnover and enhancing competitive advantage in the industry.